2021
DOI: 10.1002/lno.11877
|View full text |Cite
|
Sign up to set email alerts
|

Production and diversity of microorganisms associated with sinking particles in the subtropical North Pacific Ocean

Abstract: Sinking particulate organic matter controls the flux of carbon (C) from the surface ocean to the deep sea. Microorganisms actively colonize particles, but the extent to which microbial metabolism influences particle export remains uncertain. We conducted experiments to quantify rates of bacterial production (derived based on 3 H-leucine incorporation) and dark C-fixation (based on 14 C-bicarbonate assimilation) associated with sinking particles collected from the base of the euphotic zone (175 m) in the subtro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…It captures regional and seasonal variability in observed PSD properties, and demonstrates the ability of statistical machine learning methods to extrapolate these quantities globally. These global PSD reconstructions can in turn shed light on processes that depend on, or are reflected by, particle abundance and size distribution, including sinking particle fluxes (Guidi et al., 2008), aggregation, disaggregation and degradation of organic particles (Briggs et al., 2020; Burd & Jackson, 2009), interactions with microbial communities (Church et al., 2021; DeLong et al., 1993) and migrating animals (Cram et al., 2022), and chemical exchange between particles and seawater, including element scavenging (Ohnemus et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It captures regional and seasonal variability in observed PSD properties, and demonstrates the ability of statistical machine learning methods to extrapolate these quantities globally. These global PSD reconstructions can in turn shed light on processes that depend on, or are reflected by, particle abundance and size distribution, including sinking particle fluxes (Guidi et al., 2008), aggregation, disaggregation and degradation of organic particles (Briggs et al., 2020; Burd & Jackson, 2009), interactions with microbial communities (Church et al., 2021; DeLong et al., 1993) and migrating animals (Cram et al., 2022), and chemical exchange between particles and seawater, including element scavenging (Ohnemus et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Particles can be remineralized by microbial degradation and grazing by zooplankton (Karl et al., 1988; Giering et al., 2014; Steinberg et al., 2008), aggregate and disaggregate following physical and biological interactions (Briggs et al., 2020; Burd & Jackson, 2009; Dilling & Alldredge, 2000; Jackson, 1990; Kiørboe et al., 1990), and sink out of the surface layers to transfer carbon and nutrients to the ocean interior (Boyd et al., 2019; Buesseler et al., 2007; Turner, 2015). Marine particles are hotspots of microbial activity and diversity (Church et al., 2021; DeLong et al., 1993; Karl et al., 1984), provide the bulk of energy that sustain mesopelagic and abyssal ecosystems (Burd et al., 2010; Giering et al., 2014), and eventually supply materials to the ocean sediment, where burial sequesters them for geological timescales (Dunne et al., 2007; Sarmiento & Gruber, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Flavobacteriaceae alone could account for up to 7.74% of the total prokaryotic community at station C9. Similarly, studies in other areas also showed that many taxa in Gammaproteobacteria and Flavobacteriales were dominant in the sinking community (Baumas et al., 2021; Church et al., 2021). Systematic assessment of individual prokaryotic lineage's contribution in carbon export is also warranted.…”
Section: Discussionmentioning
confidence: 79%
“…However, these large-scale models have not explicitly included microbial ecological dynamics. This is problematic as many of the aforementioned physical and chemical mechanisms shown to impact the vertical flux of POC are controlled by microbial and grazer dynamics 22 25 , 30 . For example, lability as represented by these models is inherently related to microbial activity (as we demonstrate below).…”
Section: Introductionmentioning
confidence: 99%
“…These micro-scale observations suggest that the rate of POC consumption in the ocean is highly variable and can vary as a function of microbial processes, in contrast to the conventional representation in carbon cycle models 45 , 46 , 53 , 57 , 58 . Therefore, to mechanistically understand the vertical flux of carbon in the ocean and generate robust predictions of future changes, we must account for particle-associated microbial behavior 22 , 24 , 59 , in addition to other dynamics such as particle size distribution and zooplankton activity.…”
Section: Introductionmentioning
confidence: 99%